2016
DOI: 10.1016/j.bbmt.2015.11.350
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Human Mesenchymal Stem Cells (Remestemcel-L) on Clinical Response and Survival Confirmed in a Large Cohort of Pediatric Patients with Severe High-Risk Steroid-Refractory Acute Graft Versus Host Disease

Abstract: compared to mice receiving wild type (WT) splenocytes 1. Here, we investigate the impact of miR-155 expression in T cell migration and elucidate the T cell population responsible for miR-155 mediated modulation of aGVHD. Materials and Methods: Lethally irradiated BALB/c or B6D2F1 recipients were infused with T cell depleted WT bone marrow (BM) cells and GFP expressing miR-155 KO or GFP-B6 WT T cells. Recipients were sacrificed, organs harvested and donor T cell infiltration evaluated via confocal microscopy. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…Few patients received additional IST therapy for aGVHD during this study, further evidence of remestemcel-L effectiveness in aGVHD symptom control. Results of this study confirm the overall response, safety, and survival demonstrated in a pediatric expanded-access program study that assessed remestemcel-L in children who failed to respond to steroids and additional immunosuppressive agents for the treatment of aGVHD [26,35]. In conclusion, MSB-GVHD001 and the MSB-GVHD002 follow-up study taken together with positive findings of other remestemcel-L studies in aGVHD [26,36,40] confirm the safety profile and demonstrate the efficacy and durability of remestemcel-L treatment for SR-aGVHD in the pediatric population.…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…Few patients received additional IST therapy for aGVHD during this study, further evidence of remestemcel-L effectiveness in aGVHD symptom control. Results of this study confirm the overall response, safety, and survival demonstrated in a pediatric expanded-access program study that assessed remestemcel-L in children who failed to respond to steroids and additional immunosuppressive agents for the treatment of aGVHD [26,35]. In conclusion, MSB-GVHD001 and the MSB-GVHD002 follow-up study taken together with positive findings of other remestemcel-L studies in aGVHD [26,36,40] confirm the safety profile and demonstrate the efficacy and durability of remestemcel-L treatment for SR-aGVHD in the pediatric population.…”
Section: Discussionsupporting
confidence: 69%
“…There is a large unmet need for effective treatment. In previous studies, remestemcel-L treatment showed promising results for the treatment for SR-aGVHD in pediatric patients [26,35,36]. We report here the positive results of a prospective, multicenter, phase 3, pediatric study using remestemcel-L as first-line therapy for SR-aGVHD with long-term follow up through 180 days (MSB-GVHD002).…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Due to their potency in immune cell regulation, MSCs have been intensively tested for graft-versus-host disease and autoimmune diseases. Prochymal (later named Remestemcel-L) is the first commercial MSC product tested in phase 3 trials, in which allogeneic, cryopreserved bone marrow-derived MSCs were thawed and infused into patients with severe graft-versus-host disease 20 , 21 . There were concerns about the use of freshly thawed cells that might limit the therapeutic efficacy of the intervention 6 , 22 , 23 .…”
Section: Discussionmentioning
confidence: 99%